The use of the milk ring tet and rose Bengal test in brucellosis control and eradication in Nigeria. (2008)
In this study, milk and blood samples collected simultaneously from 532 trade cows to be slaughtered at Bodija abattoir, Ibadan (southwestern, Nigeria) were examined for antibodies to Brucella using the milk ring test (MRT) and the rose bengal test (RBT). Overall, 18.61% of the milk samples were positive according to the MRT, while 9.77 % of the serum samples were positive according to the RBT. The difference was highly significant (Chi-square value 16.33; P<0.05); only 32 (6.02 %) of the samples were positive for both tests. The Red Bororo breed of cattle and the White Fulani had the highest positive rates, namely 20.93 % and 11.69%for the MRT and RBT respectively .No conclusion can be drawn about sensitivity because we do not know the true status of the animals tested. It is, however, obvious that although the MRT and RBT are 1st-line screening tests for brucellosis in cows in some countries, their lack of specificity is of concern. Therefore, the requirement for other confirmatory tests that are more specific should be considered for control and eradication of the disease, especially in Nigeria.